DIGITAL SUBORDINATION OR SOVEREIGNTY: A COMPARATIVE ANALYSIS OF THE DIGITAL POLICIES OF THE EUROPEAN UNION, BRAZIL AND CHINA IN THE FACE OF THE HEGEMONY OF THE UNITED STATES IN THE DIGITAL ECONOMY - Siqueira Bolaño, César Ricardo; Rivero, Ezequiel Alexander; Martins do Rêgo Barreto, Helen; Medeiros, José (AoIR Selected Papers of Internet Research, 2026)
The panel discusses the responses of the European Union, Brazil, and China to the hegemony of the United States in the so-called digital economy, based on data and the operation of digital platforms. The aim is to describe and analyze these three cases about the US paradigm, problematizing the countries’ digital sovereignty in the current situation. Methodologically, the comparative analysis is based on an extensive review of the theoretical literature and case studies relating to each object, using, among other elements, document studies. It discusses how the so-called new economy is part of the latest global system of culture - an idea similar to that of the mode of regulation, with an emphasis on the articulation between material culture and spiritual culture - currently disputed by the United States and China. The panel points out that the US model, based on deregulation and the consolidation of private monopolies, has molded the global architecture of the internet and imposed a mercantile paradigm of governance, deeply linked to the speculative dynamics of capitalism under financial dominance, as will be detailed in the first contribution. The second will detail how the US project emerged victorious, going through the dispute between the technological trajectory of digital and telecommunications, the implications of which go beyond the battles over the organization of communication systems, becoming part of the struggle for socio-economic, geopolitical, and cultural hegemony. With the privatization of the internet and the centralization of capital after the dot.com crisis - which resulted in the formation of the current oligopoly of digital platforms - the new cultural system will appear, despite its unitary, globalized character and coherence with the current financial logic, to be tripartite. This is generally represented by layers: infrastructure, applications, and content. This division is useful for analyzing the position of countries, as few have trunk platforms (van Dijck, 2022), which makes the rest dependent. Faced with all the changes that have shaped the digital economy, the third contribution will analyze how Europe ended up in a position of subordination, unlike in the previous period, when European countries were gaining competition in cutting-edge industrial sectors, such as the automobile industry. This was the result, according to Nieminen, Padovani, and Sousa (2023), of a long history of public disinvestment, privatizations, deregulation, and, on the other hand, the advance of US companies in the wake of the globalization of capital. Nevertheless, the European Union has guided the so-called information society, then the knowledge society, and now the digital transition as programs associated with a possible relaunch, which has not been successful. China, on the other hand, has opted for a model of active digital sovereignty. The state has managed to develop a strategic vision of science and technology and, based on this, through different phases that will be detailed in the penultimate contribution, it has responded by creating its technological infrastructures and strengthening national companies that offer alternatives to large US corporations, configuring a model of digital autonomy. The Medium and Long Term Plan for the Development of Science and Technology (MLP) was launched in 2006 based on a broad debate on technological dependence, emphasizing the importance of endogenous innovation and the integration of science and technology development strategies with industrial policies. The 2008 global financial crisis helped accelerate this integration with the launch of Strategic Emerging Industries (SIC) in 2010. With Xi Jinping in power, in 2015 the Made in China 2025 plan was launched, covering the ten key sectors for development in the immediate future, as well as the document Guiding Opinions of the State Council for Vigorously Advancing Internet Plus Actions. In 2016, the Central Committee of the Chinese Communist Party and the State Council launched the National Innovation-Driven Development Strategy and, in 2017, it was the turn of the National New Generation Artificial Intelligence Development Plan (AIDP). In short, the proposals will result in the establishment of a particular type of relationship between the state and the platforms, as well as competition between them (WANG, Xiaoyan 2017). Finally, the panel will discuss the case of Brazil. Its recent trajectory, associated with the privatization of telecommunications, has shaped a scenario of technological dependence, where there is not even an understanding of the strategic role of digital technologies, which can be seen in the proliferation of policies that are still poorly articulated within the federal government, and the difficulty of regulating digital platforms from the National Congress. In a context of growing global concern about digital sovereignty, we are discussing the need for regulation that goes beyond merely mitigating the effects of platform dominance and explores alternative ways of strengthening digital sovereignty and development - understood, in the manner of Furtado (1967), as a creative process, based on tradition, of opening up horizons, by the goals proposed by the community and periodically renewed.